2016
DOI: 10.1038/srep29278
|View full text |Cite
|
Sign up to set email alerts
|

A consolidated analysis of the physiologic and molecular responses induced under acid stress in the legume-symbiont model-soil bacterium Sinorhizobium meliloti

Abstract: Abiotic stresses in general and extracellular acidity in particular disturb and limit nitrogen-fixing symbioses between rhizobia and their host legumes. Except for valuable molecular-biological studies on different rhizobia, no consolidated models have been formulated to describe the central physiologic changes that occur in acid-stressed bacteria. We present here an integrated analysis entailing the main cultural, metabolic, and molecular responses of the model bacterium Sinorhizobium meliloti growing under c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 105 publications
10
35
1
Order By: Relevance
“…The acid-stress response in S. meliloti has proven to be a multigenic trait (Draghi et al 2016), where several molecular changes operate in the acid-challenged rhizobia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The acid-stress response in S. meliloti has proven to be a multigenic trait (Draghi et al 2016), where several molecular changes operate in the acid-challenged rhizobia.…”
Section: Discussionmentioning
confidence: 99%
“…The observed response to acidic pH was not based on a few specific genes, but rather involved whole sets of RNAs, proteins, and metabolites associated with various cellular functions. Under the low-pH conditions imposed in the chemostat, we demonstrated that the pentose-phosphate pathway (PPP) in those cultures exhibited increases in various transcripts, enzymes, and metabolites compared to S. meliloti cells grown at neutral pH (Draghi et al 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When the amount of EPS I isolated from each of these strains was compared with the intracellular concentrations of the metabolites we determined, EPS production was positively correlated with both the hexose phosphate (R 2 ϭ 0.77) and citrate (R 2 ϭ 0.99) pools, whereas it was negatively correlated with the pentose phosphate (R 2 ϭ 0.88), lactate (R 2 ϭ 0.83), and gluconate (R 2 ϭ 0.58) pools. We note that recent metabolomic characterization of acid-tolerant growth of S. meliloti also showed that there was a correlation between EPS I production and the size of the hexose phosphate pool (43,44). Enzymatic activities can be affected by allosteric effectors and posttranslational modifications such as phosphorylation events.…”
Section: Discussionmentioning
confidence: 82%
“…Studies with Mesorhizobium loti suggested heat shock results in a global downregulation of protein expression possibly to conserve energy [99], while salt stress leads to over-expression of ABC transporters and genes associated with nucleotide transport and metabolism [100]. Similarly, characterization of the acid stress response in S. meliloti suggested that this stress results in an elevated metabolic respiration rate [101]. However, to date only a few studies have examined the responses of differentiated bacteroids to environmental stress [102,103], although several studies have examined the responses of the plant partner [104].…”
Section: Plant Growth Promoting Rhizobia In Saline and Harsh Soilmentioning
confidence: 99%